Implementasi Metode Personal Extreme Programming dalam Pengembangan Sistem Informasi Manajemen Hak Paten pada Sentra HKI ITK - Tegar Palyus Fiqar; Nur Fajri Azhar; Fathima Azzahra (LPPM ITK, 2022)
Intellectual Property Rights (IPR) are rights born of human intellectuals that have economic value. HKI can be a source of higher education funding. The Kalimantan Institute of Technology (ITK) has a HKI Center managed by the ITK LPPM (Institute for Research and Community Service). At this time, the Intellectual Property Rights Center is still not equipped with an information system for its management. The management and registration process is still carried out via email, Google Forms, and Google Sheets. HKI Centers do not yet have a system that can manage HKI Centers automatically. Thus, it is necessary to develop a Patent Management Information System (MIS) as will be discussed in this study. SIM was developed using the Personal Extreme Programming (PXP) method. The development of a patent license is expected to help simplify the process of registering and managing patents at ITK. HKI has been carried out in 5 iterations with 14 user stories. The Patent SIM implements the designs made at the design stage. Implementation is done by using the concept of Model View and Controller (MVC). Conclusions are drawn in each iteration after implementation is done. Deployment is carried out on a patent license by uploading the system to the ITK server. Patent SIM can be accessed live using the ITK network with the address hki.itk.ac.id. The system is handed over to the product owner after deployment. The development ends by conducting user training and surveys on users in each role.